THE ROLE AND PLACE OF THE NATIVE (UZBEK) LANGUAGE IN LEARNING RUSSIAN AS A FOREIGN LANGUAGE - Saidov Zhur’at Sodirovich (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2025)
This article explores the role of the native (Uzbek) language in the process of learning Russian as a foreign language. It analyzes the influence of phonetic, grammatical, and lexical features of the Uzbek language on the formation of linguistic competence in Russian. The author emphasizes the importance of taking into account the native language of learners in the methodology of teaching Russian as a foreign language and offers specific pedagogical approaches aimed at overcoming cross-linguistic interference and increasing the effectiveness of instruction.